Tourism industry political playbook in public protected areas - Ralf C. Buckley; Ratna Singh; Sonya Underdahl; Hum Gurung; Tania Romero Brito; Mary-Ann Cooper; Meisha Liddon; Zoë Jiabo Zhang; Alienor L.M. Chauvenet; Linsheng Zhong (Biological Conservation, 2026)

Rapid ecosystem service assessment of the impact of Koshi Tappu Wildlife Reserve on wetland benefits to local communities - Jennifer C. Merriman; Hum Gurung; Shalu Adhikari; Stuart H. M. Butchart; Top B. Khatri; Ravi S. Pandit; Ashok K. Ram; David H. L. Thomas; Ishana Thapa (Wetlands Ecology and Management, 2018)

Evaluating the effectiveness of conservation site networks under climate change: accounting for uncertainty - Robert Bagchi; Mike Crosby; Brian Huntley; David G. Hole; Stuart H. M. Butchart; Yvonne Collingham; Mohit Kalra; Jagadish Rajkumar; Asad Rahmani; Mitra Pandey; Hum Gurung; Le Trong Trai; et al. (Global Change Biology, 2013)
We forecasted potential impacts of climate change on the ability of a network of key sites for bird conservation (Important Bird Areas; IBA s) to provide suitable climate for 370 bird species of current conservation concern in two Asian biodiversity hotspots: the Eastern Himalaya and Lower Mekong. Comparable studies have largely not accounted for uncertainty, which may lead to inappropriate conclusions. We quantified the contribution of four sources of variation (choice of general circulation models, emission scenarios and species distribution modelling methods and variation in species distribution data) to uncertainty in forecasts and tested if our projections were robust to these uncertainties. Declines in the availability of suitable climate within the IBA network by 2100 were forecast as ‘extremely likely’ for 45% of species, whereas increases were projected for only 2%. Thus, we predict almost 24 times as many ‘losers’ as ‘winners’. However, for no species was suitable climate ‘extremely likely’ to be completely lost from the network. Considerable turnover (median = 43%, 95% CI = 35–69%) in species compositions of most IBA s were projected by 2100. Climatic conditions in 47% of IBA s were projected as ‘extremely likely’ to become suitable for fewer priority species. However, no IBA was forecast to become suitable for more species. Variation among General Circulation Models and Species Distribution Models contributed most to uncertainty among forecasts. This uncertainty precluded firm conclusions for 53% of species and IBA s because 95% confidence intervals included projections of no change. Considering this uncertainty, however, allows robust recommendations concerning the remaining species and IBA s. Overall, while the IBA network will continue to sustain bird conservation, climate change will modify which species each site will be suitable for. Thus, adaptive management of the network, including modified site conservation strategies and facilitating species' movement among sites, is critical to ensure effective future conservation.